Study: Pengukuran Saturasi Oksigen dengan Konsumer Grade RGB Kamera - Aminuddin Rizal (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2019)
Advancement on camera technology, image processing, and signal processing algorithm is widening the usage of camera into biomedical measurement. Mostly are used for pulse rate (PR) measurement to monitor human’s heart condition. In this paper, we studied the prospect of a consumer grade RGB camera as replacement for contact-based pulse oximeter (measure pulse rate and blood saturation oxygen). However, in this study we more focus on blood saturation oxygen measurement which needs more complex principle and calculation compared to PR measurement. We use both time and frequency domain calculation to know whether one or both of them have better achievement. The results reveal the summary performance from the usage of a consumer-grade RGB camera in saturation oxygen measurement.